2018
DOI: 10.3389/fphys.2018.00809
|View full text |Cite
|
Sign up to set email alerts
|

Potential Mechanisms of Action for Vitamin C in Cancer: Reviewing the Evidence

Abstract: Whether vitamin C (ascorbate) has a role to play as an anti-cancer agent has been debated for decades. Ascorbate has been used by cancer patients in an unregulated environment, either as a dietary supplement or in pharmacological doses administered by infusion, with numerous reports of clinical benefit, but in the absence of rigorous clinical trial data. The design of appropriate clinical trials has been hindered by a lack of understanding of the mechanism(s) of action that would inform the choice of effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
143
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(147 citation statements)
references
References 182 publications
1
143
0
3
Order By: Relevance
“…Guarnieri et al compared the influence of a single portion of natural vs. synthetic vitamin C on DNA damage induced by hydrogen peroxide [62]. They observed similar plasma concentrations of this vitamin in 7 volunteers, but only natural vitamin, consumed from orange juice, decreased the extent of H 2 O 2 -induced DNA damage in peripheral 4 Oxidative Medicine and Cellular Longevity blood mononuclear cells. The authors concluded that this might not be vitamin C itself that was directly responsible for the protective effects against DNA damage, but rather other compounds, like phytochemicals that might synergize the action of the vitamin or act independently of it.…”
Section: Human Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Guarnieri et al compared the influence of a single portion of natural vs. synthetic vitamin C on DNA damage induced by hydrogen peroxide [62]. They observed similar plasma concentrations of this vitamin in 7 volunteers, but only natural vitamin, consumed from orange juice, decreased the extent of H 2 O 2 -induced DNA damage in peripheral 4 Oxidative Medicine and Cellular Longevity blood mononuclear cells. The authors concluded that this might not be vitamin C itself that was directly responsible for the protective effects against DNA damage, but rather other compounds, like phytochemicals that might synergize the action of the vitamin or act independently of it.…”
Section: Human Studiesmentioning
confidence: 99%
“…Vitamin C is also reported to exert beneficial effects in the immune system and inflammation, which is crucial in fighting precancerous and cancer cells by the host (reviewed in [3]). Anticancer potential of vitamin C is suggested by the results of many other laboratory studies on experimental animals and cell cultures (reviewed in [4]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential mechanisms of action of P-AscHin cancer and clinical studies in this field were reviewed in a third 2018 paper (Vissers and Das, 2018). The authors state that there is a substantial body of literature that documents potential anti-tumor effects of ascorbate in in vitro and in vivo settings, with many reporting cytotoxicity toward cancer cells and a slowing of tumor growth in animal models.…”
Section: Clinical Safety Studies Of P-aschin Combination With Chemothmentioning
confidence: 99%
“…Current research is focussed on the identi cation and veri cation of several proposed mechanisms whereby ascorbate could affect tumour progression. These include: (i) the localised generation of cytotoxic quantities of H 2 O 2 as a consequence of ascorbate oxidation (15,18,19); (ii) ascorbatedependent activation of the 2-oxoglutarate-dependent dioxygenases that down-regulate the hypoxiainducible factors (HIFs) (20)(21)(22) and that are responsible for the demethylation of DNA and histones (11,17,(23)(24)(25) and (iii) increased oxidative stress induced by dehydroascorbic acid taken up into tumour cells via the glucose transporters (26). These mechanisms all require effective delivery of ascorbate to the tumour.…”
Section: Introductionmentioning
confidence: 99%